A anomia em um curso de formação contínua de professores de inglês da escola pública: um olhar complexo - Ravagnoli, Neiva Cristina da Silva Rego (2017)
The aim of this thesis is to describe and interpret the phenomenon anomie that can emerge from the experiences of teacher-students of graduate studies, part of a continuing education program for English teachers of community school, to understand the effects and implications of this phenomenon in that context. Anomie is a contingency that particularizes individuals’ ways of becoming, in the face of crisis situations motivated by non-conformity between individual goals and the means available to achieve these goals. This thesis, developed in the scope of Applied Linguistics, as a qualitative-interpretative research, is epistemomethodologically oriented by Morin’s Complexity and Freire’s Hermeneutic-phenomenological Complex approach: it describes and interprets textualized narratives from 32 teacher who report their experiences, according to their criteria of relevance and worldview. The anomie, object of the present study and revealed by the hermeneuticphenomenological themes: proposal, resignification and rupture, shows that this phenomenon emerges from the individual crisis experienced by teacher-students. It also emerges from the crises of the other systems in which they are situated, characterizing a moment of truth of the interrelationship between these systems, which oscillate between order and disorder. The emergence of anomia is a revealing element of the crisis and its effects. In this work, the anomie reveals the compensatory character of the continuing teacher education attributed to the CEPIEP; the depreciation of the school; the behavior of certain lecturers, allegedly not consistent with the CEPIEP course outcomes; academic solidarity shared with colleagues; and the immodest readiness and availability of certain lecturers. Anomie, as effects of the crisis, shows a movement of self-eco-organization of lecturers, which includes rupture, rejection, conformity, resignation, apathy, as well as innovation, construction, desire for change and social activism of these teachers. The anomie, when emerging from the crisis, deregulates the CEPIEP system, constraining its organizational flexibility, by teacher-students’ decision-making. At the same time, it raises responsive actions to those decisions making, which favors the regeneration of the system